Evaluasi Perbandingan Ranking Antara Proposed Value dan Perceived Value Terhadap Crowdfunding Berdasarkan Model UXHoneycomb - Muhammad Rizal Ramdhani; Hanifah Muslimah Az-Zahra; Satrio Hadi Wijoyo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Crowdfunding is a funding technique for projects or business units that involve the community at large. The concept of crowdfunding was first coined in the United States in 2003 with the launch of a site called Artistshare. In Indonesia, Crowdfunding is still not very popular, but has enormous potential to become an investment fund collection instrument. The crowdfunding application in Indonesia was used as research, namely Kitabisa, Tunaikita and Akseleran. Each offers product value to make users interested in accessing the crowdfunding application. In this study, user experience was learned from crowdfunding applications used in Indonesia. This study aims to evaluate the value of the three crowdfunding applications in Indonesia. Evaluating the third value of the Crowdfunding application, researchers used the UX Honeycomb method that can explain the quality of user experience, with 7 aspects of value in it which are accessible, findable, desirable, credible, usable, useful and valueable. From the seven values on the Honeycomb UX, a comparison of proposed value and perceived value ranks was obtained. The comparison results of proposed value and perceived value on Kitabisa have different values in accessible and useful values. Tunaikita has different values in value accessible, credible, useful and useable. Akseleran has a different value in the value of desireable, useable and valuable.